2011
DOI: 10.5897/ajmr11.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cELISA and IFA tests in the serodiagnosis of anaplasmosis in cattle

Abstract: This study was performed to compare indirect fluorescence antibody (IFA) test with competitive ELISA (cELISA) for detection of antibodies to Anaplasma marginale in cattle. In this study, a total of 484 cattle were examined on farms that had a positive history of anaplasmosis. Thin blood smears were prepared from each examined cattle and the cELISA and IFA tests were performed. Samples in which the results of microscopic examination and cELISA were compatible were used as a "gold standard" to define sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…in sheep [13,40,41]. Recently, Ab-IFAT was shown to have high sensitivity (100%) and specificity (91.9%) when compared to the combination of microscopic examination and cELISA, while a previous study reported a similar level of specificity and sensitivity for Ab-IFAT when compared with cELISA [15,17].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…in sheep [13,40,41]. Recently, Ab-IFAT was shown to have high sensitivity (100%) and specificity (91.9%) when compared to the combination of microscopic examination and cELISA, while a previous study reported a similar level of specificity and sensitivity for Ab-IFAT when compared with cELISA [15,17].…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, diagnosis through blood smear cytological examination may not be feasible to identify carrier animals. Thus, serological assays, such as indirect immunofluorescence antibody (Ab-IFAT), enzyme-linked immunosorbent assay (ELISA) and complement fixation tests (CF), have been used for the detection of anti-Anaplasma antibodies [11][12][13][14][15]. Among the various serological techniques, competitive ELISA (cELISA) presents high sensitivity and specificity for the detection of Anaplasma-specific antibodies [16], while the Ab-IFAT has been commonly used in epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%